2016
DOI: 10.1038/srep32088
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of open chromatin in bidirectional promoters of rice

Abstract: Bidirectional gene pairs tend to be highly coregulated and function in similar biological processes in eukaryotic genomes. Structural features and functional consequences of bidirectional promoters (BDPs) have received considerable attention among diverse species. However, the underlying mechanisms responsible for the bidirectional transcription and coexpression of BDPs remain poorly understood in plants. In this study, we integrated DNase-seq, RNA-seq, ChIP-seq and MNase-seq data and investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
(96 reference statements)
2
15
0
Order By: Relevance
“…In addition, the percentage of coexpressed gene pairs decreased with increasing BDP size (Additional file 6 : Table S6). The highest frequency of coexpression was previously found in gene pairs separated by 200 bp [ 32 ], here we further observed that gene pairs were generally more frequently coexpressed when the intergenic distance was less than 500 bp. (Additional file 7 : Figure S1).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…In addition, the percentage of coexpressed gene pairs decreased with increasing BDP size (Additional file 6 : Table S6). The highest frequency of coexpression was previously found in gene pairs separated by 200 bp [ 32 ], here we further observed that gene pairs were generally more frequently coexpressed when the intergenic distance was less than 500 bp. (Additional file 7 : Figure S1).…”
Section: Resultssupporting
confidence: 77%
“…To comprehensively characterize the DNA sequence profiles of the BDPs in rice, we first identified bidirectional gene pairs with head-to-head orientations using the updated version of the rice genome (The Institute for Genomic Research (TIGR), rice subsp. Japonica version 7.0) as described previously [ 32 ], which contains a total of 55,801 annotated genes. We identified a total of 290 type I BDPs, 294 type II BDPs (BDPs II) and 627 type III BDPs (BDPs III), with TSS intergenic distances of 0–250 bp (BDPs I), 250–500 bp (BDPs II) and 500–1000 bp (BDPs III), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Histone modification data, including H3K4me3, H3K27me3 were retrieved from GSE19602 [38], and the H3K27ac, H3K9me3 were retrieved from GSE79033 [39], the H3K4me1 was retrieved from GSA under accession no. PRJCA000387 [40].…”
Section: Methodsmentioning
confidence: 99%